Long term monitoring of the extreme intraday variable quasar PKS 0405-385 - Kedziora-Chudczer, L; Jauncey, D; Lovell, J; Walker, M; Macquart, J; Wieringa, M; Tzioumis, A; Perley, R; Reynolds, J (2002)
The quasar PKS 0405-385 exhibits episode's of unusually strong hourly variability at 8.6, 4.8, 2.4 and 1.4 GHz. These variations, seen first in June 1996, ceased after several weeks, but reappeared in November 1998 and were monitored closely at the. ATCA. We argue that our data are in agreement with interstellar scintillation of a source component which is a few micro-arcseconds in size. This claim is further supported by our recent finding of the time delay in the variability pattern measured between the ATCA and the VLA.